2002
DOI: 10.1080/09537320220125874
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Innovations in Small and Medium Sized Enterprises

Abstract: Supporting and accelerating the adoption and diffusion of environmental innovations amongst small and medium sized enterprises (SMEs) is a major challenge to environmental policy makers. Research suggests that whilst SMEs possess high flexibility, their innovative capacity may be limited to incremental changes within their existing technology system and network. Twenty case studies examining the innovation adoption process in SMEs in four sectors and in five countries within the ENVIS project (commissioned by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 3 publications
2
36
0
6
Order By: Relevance
“…Hillary (2004) 8 EU countries SME 1-249 survey (unclear, approx. 120 SMEs) Peters & Turner (2004) UK no clear SME definition interview (62 SMEs) Pimenova & van der Vorst (2004) UK micro 1-9, SME 10-249 survey (13 micro, 9 SMEs) Rothenberg & Becker (2004) USA small <= 20, medium > 20 survey (54 small, 74 medium) interview (7 SMEs, 9 advisers) Simpson et al (2004), Taylor et al (2003) UK SME < 250 survey (63 SMEs) interview, site visit (15 SMEs) Ammenberg & Hjelm (2003) Sweden SME 0-249 interviews (25 SMEs) Kannan & Boie (2003) Germany SME < 500 case study (1 SME) Lefebvre et al (2003) Canada SME < 500 survey (368 SMEs) Naffziger et al (2003) USA SME <= 500 survey (100 SMEs) Revell (2003) Japan small < 50 interview (20 small) Vernon et al (2003) UK micro < 10 focus group (25 micro, 34 staff) Friedman & Miles (2002) UK SME < 250 interview (61 SMEs, 21 stakeholders) Gunningham & Sinclair (2002) Australia small < 50 interview (13 small, 8 stakeholders) Hansen et al (2002) 5 EU countries SMEs <= 250 interview (20 SMEs) Schaper (2002) Australia small < 20 survey (154 small) Rutherfoord et al (2000) UK, Netherlands small < 50 interview (40 small) Tilley (2000), Tilley (1999) UK small < 50 interview (60 small) Non-empirical journal articles Clement & Hansen (2003) Content analysis of documents on Nordic SME environmental funding schemes Hoevenagel & Wolters (2000) Secondary data on Dutch SME (< 100 staff) use of environmental intermediaries Shearlock et al (2000) Studied a database of environmental service firms, but not SMEs using the services Walley & Taylor (2002) Literature review which identified and defined a typology of green entrepreneurs…”
Section: Methodsmentioning
confidence: 99%
“…Hillary (2004) 8 EU countries SME 1-249 survey (unclear, approx. 120 SMEs) Peters & Turner (2004) UK no clear SME definition interview (62 SMEs) Pimenova & van der Vorst (2004) UK micro 1-9, SME 10-249 survey (13 micro, 9 SMEs) Rothenberg & Becker (2004) USA small <= 20, medium > 20 survey (54 small, 74 medium) interview (7 SMEs, 9 advisers) Simpson et al (2004), Taylor et al (2003) UK SME < 250 survey (63 SMEs) interview, site visit (15 SMEs) Ammenberg & Hjelm (2003) Sweden SME 0-249 interviews (25 SMEs) Kannan & Boie (2003) Germany SME < 500 case study (1 SME) Lefebvre et al (2003) Canada SME < 500 survey (368 SMEs) Naffziger et al (2003) USA SME <= 500 survey (100 SMEs) Revell (2003) Japan small < 50 interview (20 small) Vernon et al (2003) UK micro < 10 focus group (25 micro, 34 staff) Friedman & Miles (2002) UK SME < 250 interview (61 SMEs, 21 stakeholders) Gunningham & Sinclair (2002) Australia small < 50 interview (13 small, 8 stakeholders) Hansen et al (2002) 5 EU countries SMEs <= 250 interview (20 SMEs) Schaper (2002) Australia small < 20 survey (154 small) Rutherfoord et al (2000) UK, Netherlands small < 50 interview (40 small) Tilley (2000), Tilley (1999) UK small < 50 interview (60 small) Non-empirical journal articles Clement & Hansen (2003) Content analysis of documents on Nordic SME environmental funding schemes Hoevenagel & Wolters (2000) Secondary data on Dutch SME (< 100 staff) use of environmental intermediaries Shearlock et al (2000) Studied a database of environmental service firms, but not SMEs using the services Walley & Taylor (2002) Literature review which identified and defined a typology of green entrepreneurs…”
Section: Methodsmentioning
confidence: 99%
“…These innovations also encourage improved productivity (Biondi and Iraldo 2002), the implementation of continuous improvement processes (King and Lenox 2002;van Berkel 2007), and external partnerships (Hansen et al 2002). These innovative practices in the environmental field are thus also linked to innovations at the level of human resource and community relations.…”
Section: Entrepreneurial Orientation and Sustainable Practicesmentioning
confidence: 99%
“…Identifying an SME's specific eco-innovation strategy helps to understand why it chooses to engage in eco-innovation, for example, increasing the eco-efficiency of their production processes, and in which ways this influences organizational, product, and/or process innovations. As is pointed out by Hansen, Sondergard and Meredith (2002):…”
Section: Eco-innovation In Smes From a Strategy Perspectivementioning
confidence: 80%
“…Ecoprofit pushed these SMEs out of their initial comfort zone by enabling them to recognize and develop a more explicit strategic interpretation of future opportunities for eco-innovation (see Hansen, Sondergard and Meredith 2002). Moreover, the SMEs made competencies available, engaged in some networking activities, and continued to engage in eco-innovations years after Ecoprofit participation.…”
Section: An Overview Of the Three Patterns Of Green Strategy Developmmentioning
confidence: 99%
See 1 more Smart Citation